2019
DOI: 10.1002/chem.201903142
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Redox Active Polyoxometalates for Efficient Electron‐Coupled Proton‐Buffer‐Mediated Water Splitting

Abstract: We present strategies to tune the redox properties of polyoxometalate clusters to enhance the electron‐coupled proton‐buffer‐mediated water splitting process, in which the evolution of hydrogen and oxygen can occur in different forms and is separated in time and space. By substituting the heteroatom template in the Keggin‐type polyoxometalate cluster, H6ZnW12O40, it is possible to double the number of electrons and protonation in the redox reactions (from two to four). This increase can be achieved with better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 36 publications
0
46
0
Order By: Relevance
“…[1,3]. Among them, catalysts-assisted water splitting is one of the most promising methods to generate hydrogen [8][9][10]. Precious metals (platinum and palladium based) are common catalysts for water splitting, and the onset potential of the Pt electrode is close to 0 mV [11].…”
Section: Introductionmentioning
confidence: 99%
“…[1,3]. Among them, catalysts-assisted water splitting is one of the most promising methods to generate hydrogen [8][9][10]. Precious metals (platinum and palladium based) are common catalysts for water splitting, and the onset potential of the Pt electrode is close to 0 mV [11].…”
Section: Introductionmentioning
confidence: 99%
“…[47,48] In 2019, Lei et al conducted a comparative study of three allied tungstenbased Keggin polyoxometalates of the form [XW 12 O 40 ] (where X = P 5+ , Si 4+ , or Zn 2+ ), in order to ascertain the effect of the central heteroatom on the redox properties of the clusters. [49] By reductive bulk electrolysis, the authors confirmed the twoelectron nature of the reductions of both phosphotungstic acid and silicotungstic acid but found that the Zn 2+ analogue, H 6 ZnW 12 O 40 , was able to undergo reduction by up to four electrons under the same conditions. There was no significant change in pH during this reduction (or the subsequent electrochemical reoxidation), suggesting that H 6 ZnW 12 O 40 is an effective Electron-Coupled-Proton Buffer.…”
Section: Other Polyoxometalatesmentioning
confidence: 93%
“…Some key metrics of the decoupling agents for water splitting discussed in this review. Symes and Cronin [28] Bloor et al [34] Li et al [38] H 4 [SiW 12 O 40 ] 0.0, -0.22 0.5 9 95 ± 7% 100% Rausch et al [43] Chisholm et al [44] Wu et al [85] H 3 PW 12 O 40 +0.237, -0.036 0.42 -44.6% -Macdonald et al [46] H 4 SiO 4 •12MoO 3 +0.509 0.69 ---Macdonald et al [46] H 6 ZnW 12 O 40 -0.078 -0.198 0.4 200 95.5% -Lei et al [49] [P 2 W 18 O 62 ] 6-+0.3, +0.1, 0 to -0.5 1 100 --Chen et al [50] V(III)/V(II) -0.26 0 -96 ± 4% -Amstutz et al [51] Ho et al [53] Ce(IV)/Ce(III) +1.48 0 --78 ± 8% Amstutz et al [51] Fe(CN) 6 3-/Fe(CN) 6…”
Section: Phosphomolybdic Acidmentioning
confidence: 99%
“…As a result, they can be used in the electrochemical field. Proton conductivity is another remarkable property of PCMs, allowing them to be used in modern perspectives, such as proton-exchange membrane fuel cells [10,11,14]. POMs, on the other hand, have been discovered to play a key part in the extraordinary development of PCMs having greater efficiency and stability.…”
Section: Abstract a R T I C L E I N F O R M A T I O Nmentioning
confidence: 99%
“…POMs, on the other hand, have been discovered to play a key part in the extraordinary development of PCMs having greater efficiency and stability. PCMs are also being used to create neoteric smart structures for applications such as optics [10,11,14], pharmaceuticals [15][16][17], energy-related applications [18][19][20], sensors [21][22][23], and green catalysis [24][25][26] (Fig. 1).…”
Section: Abstract a R T I C L E I N F O R M A T I O Nmentioning
confidence: 99%